The phenomenon of femicide: a systematic review - Ochoipoma Guerrero, Jonathan Harry (2022)
The main objectives of this article are to determine the definition of femicide and identify its causes and types. For this, a systematic investigation was carried out where 164 articles were found, of which 123 were disregarded because they did not meet the inclusion criteria, and 41 articles were selected: 26 from Scopus and 15 from Scielo. The data was processed through Microsoft Excel software. As a result of this, the main results obtained were: 81.82% of the selected articles used the murder of women as a frequent term, 33.33% determined that the most frequent cause of femicide is jealousy and 100% of the selected articles identified that the most frequent type of femicide is intimacy. For this reason, it is concluded that there are similar elements in the concepts of femicide analyzed, jealousy is the most frequent cause of femicide and the intimacy and non-intimacy types predominate in the selected articles.